FLUID CATASTROPHE - REID, JOHN (CAMBRIDGE SCHOLARS PUBLIS, 2019)
By abandoning classical theory and adopting a liberating, empirical approach to fluid behaviour, this book sheds new light on Global Warming, on Ice Ages, why the wind makes waves bigger, and the origin of the Earth's magnetic field. At heart, it is concerned with how meaning can be extracted from a sequence of measurements--time series analysis. The methods developed (plus Python code) will appeal to both the graduate student and the data analyst. The ""Ultraviolet Catastrophe"", the failure to account for black-body radiation, led to quantum mechanics. Another catastrophe was politely ignore.